Nitric oxide-induced stromal depletion for improved nanoparticle penetration in pancreatic cancer treatment. (July 2020) - Chen, Xiaohui; Jia, Fan; Li, Yongzhou; Deng, Yongyan; Huang, Yue; Liu, Weifeng; Jin, Qiao; Ji, Jian
Abstract: Abundant desmoplastic stroma, which typically exists in pancreatic ductal adenocarcinoma (PDAC), can act as a natural protective physical barrier rendering insufficient drug delivery and penetration. To address this issue, we herein report a two-step sequential delivery strategy for enhanced pancreatic cancer therapy. In this sequential strategy, the nitric oxide (NO) donor S-nitroso- N -acetylpenicillamine (SNAP) loaded liposomes (Lip-SNAP) were firstly delivered to pancreatic stellate cells (PSCs) in tumor tissue to inhibit the production of dense stroma, by inhibiting the expression of TGF-β1 and its downstream profibrotic signal transduction. Therefore, the PSC-mediated desmoplastic reaction could be suppressed by inhibiting the expression of fibronectin, α-SMA and collagen. The gemcitabine (GEM) loaded liposomes (Lip-GEM) were administrated subsequently. The enhanced intratumoral penetration of Lip-GEM was then achieved due to the stromal disruption in consequence of NO treatment, thus significantly improving the drug delivery efficiency. The tumor growth inhibition of the two-step sequential delivery of Lip-SNAP and Lip-GEM was investigated on both subcutaneous and orthotopic tumor mouse models, to show the remarkably improved therapeutic efficacy of GEM. Such NO-induced stromal depletion provides a general strategy to overcome the blockage of desmoplastic stroma on other therapeutic agents.